Chaotic ratchet dynamics with cold atoms in a pair of pulsed optical lattices - Carlo, Gabriel Gustavo (2006)
We present a very simple model for realizing directed transport with cold atoms in a pair of periodically flashed optical lattices. The origin of this ratchet effect is explained and its robustness demonstrated under imperfections typical of cold atom experiments. We conclude that our model offers a clear-cut way to implement directed transport in an atom optical experiment.